Mechanisms Involved In The Biological Control Of Tomato Bacterial Wilt Caused By Ralstonia Solanacearum Using Arbuscular Mycorrhizal Fungi - Mohumad Tahat, Monther (2009)

(untitled)
Glasshouse experiment was done to study the ability of two local mycorrhizal fungi species (Glomus mosseae, Scutellospora sp.,) and introduced species (Gigaspora margarita) to colonize and enhance some tomato growth parameters. G. mosseae showed the best preformance among species used. G. mosseae was able to increase significantly plant height (60% ), shoot dry weight (135%) and flowers number (58%) compared to the control plant at the 7th weeks of plant growth. G. mosseae alter root structures such as root dry weight (42%), root tips (120%), root length(83%), root surface area (106%), and root volume (59%), which can increase nutrient absorption and enhance plant growth. G. mosseae was adapted to the local environmental conditions which resulted in more root colonization (300%) and more spores number (300%), different from the introduced species G. margarita. The overall data presented in this study showed that local species can be used for enhancing yield growth more than the introduced species. Three mechanisms were described to explain by how arbuscular mycorrhizal fungi (AMF) inhibit or control the bacterial wilt disease. Nutrient uptake, biochemical changes and root morphological changes were the mechanisms studied. The concentrations of N (41%), P (133%), K (49%), Fe (44%), and Zn (33%) in tomato shoots were increased after the colonization of G. mosseae, indicating that AMF was able to increase the shoot nutrient uptake due to the hyphal net were produced by AMF which allow the roots to absorb more nutrient. The root morphological characteristics (root dry weight, root tips, root volumes, root length and root surface area) were changed significantly in G. mosseae treatment compared to all other treatments. The SEM and TEM images provided evidence that AMF can modify the root cortex cells and root structure which finally helps the plant to prevent the disease infection totally. The G. mosseae hyphal structures were seen inside the cortex cell. Disease symptoms were not seen in the G. mosseae +R. solanacearum treated plants. The extensive colonization by AMF was the reason behind the high concentration of chlorophyll (a) and chlorophyll (b) which could contribute to the increase of photosynthetic rate in tomato leaves and enhance plant growth. Ch.(a) and ch.(b) in G. mosseae treated plants was significantly higher compared to the rest of the treatments. G. mosseae can be used as a bio-protection agent because it can provide root with hyphal net which can minimize the bacterial wilt infection. The production of healthy, huge number and clean G. mosseae spores were the targets of another glasshouse experiment. The results obtained from this experiment showed that the harvest date and the type of the crops were played a critical role in AMF spore production. Corn was the most suitable host for G. mosseae sporulation (167 spore/10gm soil). Lentil, green bean, and barley showed low AMF sporulation and colonization related to the inability of these crops to grow under glasshouse conditions. Several important factors must be considered in AMF mass production, included plant host species, environmental conditions, soil types, nutrient regime, pot size, inoculum amount and the source of primary inoculum. In vitro experiments were done to study the effects of different root exudates with and without pre-inoculation with G. mosseae on the control of R. solanacearum and to study the indirect interaction between G. mosseae and R. solanacearum. In general, the influence of root exudates produced from tomato and corn plants on G. mosseae spore germination showed different response. The spores germination number was decreased using different volumes of mycorrhizal tomato root exudates (MTRE) and mycorrhizal corn root exudates (MCRE). It was increased when non-mycorrhizal tomato root exudates (NMTRE) and non-mycorrhizal corn root exudates (NMCRE) were applied in different volumes. G. mosseae spores germinated in all types of media used. The spore germination number was increased by increasing the original number of spores cultured and this indicated that the volatiles compounds produced from bacterial pathogen did not inhibit the spore's germination. The overall results concluded from these studies confirm that the local species of AMF were more able to support and enhance plant growth compared to the introduced species. G. mosseae was able to control totally the bacterial wilt causal agent R. solanacearum under glasshouse conditions. Nutrient uptake, biochemical changes and root morphological changes were the three mechanism tested. The production of huge number of AMF spores is a critical area for mycorrhizal research using suitable host plant as a trap.